IKLIM ORGANISASI DAN KOMITMEN ORGANISASI DOSEN UNIVERSITAS NEGERI JAKARTA - MAUNA MAUNA; AMANDA TIARA SARI (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2016)
This study aims to examine empirically whether there is influence between psychological climate to organizational commitment. The subject were 221 lecturer of State University of Jakarta (UNJ) selecting using incidental sampling technique. This type of research is a quantitative research, data collection techniques using research data obtained through survey instruments/questionnaire adaption from previous researchers. Instruments made have been tested for validity and reliability, and belonging to the reliable criteria. Research hypothesis testing was performed using linear regression analysis of the predictors, with the psychological climate as a predictor variable. The analysis shows a correlation coefficient of 0,000, less than the significance level (0.05). This value is interpreted that there are significant psychological climate to organizational commitment. The coefficient of determination shows rxy2 value of 0.301, meaning that there is a 30,1% variance tendency of psychological climate on. So this research indicates that the lecturer will indicate the optimal organizational commitment if it has high psychological climate.